1998
DOI: 10.1086/301917
|View full text |Cite
|
Sign up to set email alerts
|

Acromesomelic Dysplasia Maroteaux Type Maps to Human Chromosome 9

Abstract: Acromesomelic dysplasias are skeletal disorders that disproportionately affect the middle and distal segments of the appendicular skeleton. We report genetic mapping studies in four families with acromesomelic dysplasia Maroteaux type (AMDM), an autosomal recessive osteochondrodysplasia. A peak LOD score of 5.1 at recombination fraction 0 was obtained with fully informative markers on human chromosome 9. In three of the four families, the affected offspring are products of consanguineous marriages; if it is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 26 publications
1
30
0
1
Order By: Relevance
“…Today it is agreed that very likely these conditions are allelic forms of the same disorder. Many previous studies have shown that the short arm of chromosome 9 and in particular the region 9p12-p13 plays an important role in a large number of common diseases, such as acute lymphoblastic leukaemia, 11 non-Hodgkin's lymphoma, 12 lung cancer, 13 hepatocellular carcinoma (HCC), 14 as well as in rare diseases, such as arthrogryposis multiplex congenita, distal, type 1 (AMCD1), 15 acromesomeric dysplasia (AMDM), 16 cartilage hair hypoplasia (CHH), 17 and also in a form of distal hereditary motor neuropathy (HMN) found in Jerash. 18 At present, the availability of a precise physical map of chromosome 9p12-p13 is very restricted, and very few mapped genes have been identified in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Today it is agreed that very likely these conditions are allelic forms of the same disorder. Many previous studies have shown that the short arm of chromosome 9 and in particular the region 9p12-p13 plays an important role in a large number of common diseases, such as acute lymphoblastic leukaemia, 11 non-Hodgkin's lymphoma, 12 lung cancer, 13 hepatocellular carcinoma (HCC), 14 as well as in rare diseases, such as arthrogryposis multiplex congenita, distal, type 1 (AMCD1), 15 acromesomeric dysplasia (AMDM), 16 cartilage hair hypoplasia (CHH), 17 and also in a form of distal hereditary motor neuropathy (HMN) found in Jerash. 18 At present, the availability of a precise physical map of chromosome 9p12-p13 is very restricted, and very few mapped genes have been identified in this region.…”
Section: Introductionmentioning
confidence: 99%
“…The gene encodes a 1047 amino acid protein (Kant et al, 1998). The protein product of the NPR2 gene (natriuretic peptide receptor B) is a receptor for CNP.…”
Section: Discussionmentioning
confidence: 99%
“…The skull is usually dolichocephalic with shortness of the trunk and reduced vertebral height without any associated facial or mental abnormalities (Langer & Garrett, 1980). Kant et al (1998) mapped AMDM on human chromosome 9p21-p12. Bartels et al (2004) later reported 21 mutations in the NPR2 gene underlying AMDM in 21 different families.…”
Section: Introductionmentioning
confidence: 99%
“…In this syndrome, affected subjects are normal at birth, develop short-limbed (disproportionate) short stature in the subsequent 1–2 years and attain a final adult height of approximately 95–125 cm (3–4 feet) (fig. 2) [23, 24]. Apart from the skeletal system, no other organ system abnormality has been identified so far in humans [22].…”
Section: Genetic Evidence Linking Natriuretic Peptides With Skeletal mentioning
confidence: 99%